Teknik Penetasan Artemia dan Produksi Cacing Tubifex Sebagai Pakan Alami Ikan Di Desa Hagu Teungoeh Melalui Penyuluhan dan Pelatihan - Salamah, Salamah; Mahdaliana, Mahdaliana; Hatta, M.; Ayuzar, Eva; Makarti Muktitama, Asih; Risna, Dewi (Aceh Journal of Community Engagement (AJCE), 2024)
The death of fish in the fry phase or larvae at the beginning of rearing is caused by the fish's ability to digest artificial feed given by farmers, because in the fry phase the fish's digestive tract is not yet fully formed so it needs to be given natural feed which has autolysis properties. Meanwhile, pellet feed or feed that has been given by farmers in the seed phase does not have autolysis properties, causing farmers to experience losses due to death at the start of cultivation. The procedure for this community service activity consists of several stages, namely: (1) Counseling about natural fish food, namely brine shrimp and tubifex worms, (2) counseling about the introduction of various tools and materials that can be used as a medium for growing natural food, (3) counseling about natural food production technology, (4) training on the stages of designing containers and growing media for natural food, and (5) training on natural food production. As a result of the outreach from this activity, the community can understand artemia hatching techniques and tubifex worm production so that they can be used as fish feed during the hatchery period. With this training, the community can carry out the process of artemia hatching and tubifex worm production using raw materials available around them so that the community can increase the production of natural feed.